Long-term exposure of 2450 MHz electromagnetic radiation induces stress and anxiety like behavior in rats. (September 2019) - Gupta, Sukesh Kumar; Patel, Shishir Kumar; Tomar, Munendra Singh; Singh, Shio Kumar; Mesharam, Manoj Kumar; Krishnamurthy, Sairam
Abstract: Long term exposure of electromagnetic radiations (EMR) from cell phones and Wi-Fi hold greater propensity to cause anxiety disorders. However, the studies investigating the effects of repeated exposure of EMR are limited. Therefore, we investigated the effects of repeated exposure of discrete frequencies of EMR in experimental animals. Male rats were exposed to EMR (900, 1800 and 2450 MHz) for 28 (1 h/day) days. Long term exposure of EMR (2450 MHz) induced anxiety like behavior. It deregulated the hypothalamic pituitary adrenal (HPA) axis in rats as observed by increase in plasma corticosterone levels apart from decreased corticotrophin releasing hormone-2 (CRH-2) and Glucocorticoid receptor (GR) expression in amygdala. Further, it impaired mitochondrial function and integrity. The expression of Bcl2 showed significant decrease while Bax and ratio of Bax: Bcl2 were increased in the mitochondria and vice versa in cytoplasm indicating altered regulation of apoptosis. EMR exposure caused release of cytochrome-c and expression of caspase-9 ensuing activation of apoptotic cell death. Additional set of experiments performed to estimate the pattern of cell death showed necrotic and apoptotic amygdalar cell death after EMR exposure. Histopathological studies also revealed a significant decrease in neuronal cells in amygdala. The above findings indicate that long-term exposure of EMR radiation (2450 MHz) acts as a stressor and induces anxiety-like behaviors with concomitant pathophysiological changes in EMR subjected rats. Graphical abstract: Image 1 Highlights: EMR-2450 MHz induces stress and aggravates anxiety-like symptoms in rats. Exposure of EMR-2450 MHz increases plasma corticosterone level and, expression of CRH-2 and GR in amygdala. Increased expression of cytochrome-C and caspase-9 indicating mitochondrial dysfunction and activation of apoptosis. Change in expression of mitochondrial Bax: Bcl2 ratio indicating modulation of apoptosis. EMR-2450 MHz exposure causes both amygdalar necrotic and apoptotic cell death.